2006
DOI: 10.1016/j.devcel.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A Viral Protein that Blocks Arf1-Mediated COP-I Assembly by Inhibiting the Guanine Nucleotide Exchange Factor GBF1

Abstract: Many viruses modify cellular processes for their own benefit. The enterovirus 3A protein inhibits endoplasmic reticulum (ER)-to-Golgi transport, a function previously suggested to be important for viral suppression of immune responses. Here, we show that a virus carrying a 3A protein defective in inhibiting ER-to-Golgi transport is indeed less virulent in mice, and we unravel the mechanism by which 3A inhibits this trafficking step. Evidence is provided that 3A inhibits the activation of the GTPase ADP-ribosyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
235
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(249 citation statements)
references
References 46 publications
14
235
0
Order By: Relevance
“…To this end, we co-transfected cells with plasmids encoding FAPP1-PH-GFP together with wt or mutant 3A-myc, and one day later treated them for 1 h with the compounds. In untreated cells, wt 3A was visible in a punctate pattern ( Figure 6A), corresponding to a localization to dispersed Golgi membranes, as previously described [20,23]. 3A showed a great overlap with PI4P, as detected by FAPP1-PH-GFP.…”
Section: Mutations In 3a Do Not Rescue the Activity Of Pi4kiiiβ In Thmentioning
confidence: 67%
See 2 more Smart Citations
“…To this end, we co-transfected cells with plasmids encoding FAPP1-PH-GFP together with wt or mutant 3A-myc, and one day later treated them for 1 h with the compounds. In untreated cells, wt 3A was visible in a punctate pattern ( Figure 6A), corresponding to a localization to dispersed Golgi membranes, as previously described [20,23]. 3A showed a great overlap with PI4P, as detected by FAPP1-PH-GFP.…”
Section: Mutations In 3a Do Not Rescue the Activity Of Pi4kiiiβ In Thmentioning
confidence: 67%
“…As primary antibodies we used rabbit polyclonal anti-PI4-KinaseIIIβ (Upstate), mouse monoclonal anti-GBF1 (BD Biosciences), rabbit polyclonal anti-Arf1 (kind gift from dr. F. Wieland, Biochemie-Zentrum Heidelberg, Germany), mouse monoclonal anti-c-Myc (Sigma Aldrich), mouse monoclonal anti-dsRNA (J2, English & Scientific Consulting), mouse anti-PI4P IgM (Echelon Biosciences), mouse monoclonal anti-HA (Covance), mouse monoclonal anti-β-actin (Sigma), and rabbit polyclonal anti-CVB3 3A described previously [23]. The secondary antibodies for immunofluorescence included Alexa Fluor 488-or 594-conjugated goatanti-rabbit IgG, Alexa Fluor 488-or 594-conjugated goat-antimouse IgG, or Alexa Fluor 594-conjugated goat-anti-mouse IgM (Molecular Probes).…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…ARF1, GBF1, and COPI during their successful replication [6,16]. The overexpression of Arf1 or GBF1 reversed the effects of coxsackie virus 3A protein by not inhibiting the trafficking in between ER-Golgi [33]. Yamayoshi et al [37] also showed that dominant-negative mutants of the GTPase Rab1b inhibited the Ebola virus matrix protein VP40-mediated particle formation, consistent the use of this vesicular pathway in the exit of this filovirus.…”
Section: Discussionmentioning
confidence: 95%
“…For viral protein synthesis, recruitment of ribosome to the internal ribosomal entry site (IRES) on the viral genome requires host factors polypyrimidine tract-binding protein (PTB), Unr, La, poly(rC)-binding protein 2 (PCBP2) and SRp20 that are not required for cap-dependent protein synthesis of cellular mRNA (Bedard et al, 2007;Hellen et al, 1993;Hunt et al, 1999;Meerovitch et al, 1993;Sanford et al, 2004;Walter et al, 1999), along with proteolytic modification of a translation initiation factor eIF4G by viral proteinase 2A pro to hijack the translation machinery from cap-dependent protein synthesis to viral protein synthesis (Gradi et al, 1998;Krausslich et al, 1987). For the replication process, membrane rearrangement utilizing ADP ribosylation factors (Arfs) and guanine nucleotide exchange factors (GEFs) (GBF1, BIG1/2) are required via direct and indirect interaction with viral 3A and 3CD proteins in coxsackievirus B3 (CVB3) and PV infections (Belov et al, 2007;Wessels et al, 2006). Cellular signalling via extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase (PI3K) and stress-activated protein kinases (SAPKs) affected replication and/or the release of progeny virus in CVB3 infection by an unknown mechanism (Esfandiarei et al, 2004;Luo et al, 2002;Si et al, 2005).…”
Section: Introductionmentioning
confidence: 99%